Analisis Faktor-Faktor yang Mempengaruhi Pengobatan Pasien TB di Puskesmas PB Selayang II Kota Medan - Monica Silviyana Simbolon; Erida Novriani; Razoki (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Tuberculosis (TB) is an infectious disease that is one of the leading causes of death in the world. Indonesia ranks second highest in global TB cases, with Medan City being one of the areas with significant cases. This study aims to analyze the factors that influence the treatment of TB patients at the PB Selayang II Health Center in Medan City. The study used a qualitative descriptive method with an in-depth interview approach to ten TB patients until information saturation was reached. The results of the analysis showed that the factors that most influenced the treatment of TB patients were compliance, knowledge, and demographic factors such as age, educations. Family support, personal motivation, and the role of health workers also play an important role in the success of treatment. This study concludes that interventions to improve patient compliance and knowledge, as well as paying attention to socio-economic conditions, are very important in TB control programs at the primary health care level.